Return-to-activity after anatomical reconstruction of acute high-grade acromioclavicular separation. Issue 1 (December 2016) - Saier, T.; Plath, J.; Beitzel, K.; Minzlaff, P.; Feucht, J.; Reuter, S.; Martetschläger, F.; Imhoff, Andreas; Aboalata, M.; Braun, S.
Abstract Background To evaluate return-to-activity (RtA) after anatomical reconstruction of acute high-grade acromioclavicular joint (ACJ) separation. Methods A total of 42 patients with anatomical reconstruction of acute high-grade ACJ-separation (Rockwood Type V) were surveyed to determine RtA at a mean 31 months follow-up (f-u). Sports disciplines, intensity, level of competition, participation in overhead and/or contact sports, as well as activity scales (DASH-Sport-Module, Tegner Activity Scale) were evaluated. Functional outcome evaluation included Constant score and QuickDASH. Results All patients (42/42) participated in sporting activities at f-u. Neither participation in overhead/contact sports, nor level of activity declined significantly (n.s.). 62 % (n = 26) of patients reported subjective sports specific ACJ integrity to be at least the same as prior to the trauma. Sporting intensity (hours/week: 7.3 h to 5.4 h, p = .004) and level of competition (p = .02) were reduced. If activity changed, in 50 % other reasons but clinical symptoms/impairment were named for modified behavior. QuickDASH (mean 6, range 0–54, SD 11) and DASH-Sport-Module (mean 6, range 0–56, SD 13) revealed only minor disabilities at f-u. Over time Constant score improved significant to an excellent score (mean 94, range 86–100, SD 4;p < .001). Functional outcome was not correlated with RtA (n.s.). Conclusion All patients participated in sporting activities after anatomical reconstruction of high-grade (Rockwood Type V) ACJ-separation. With a high functional outcome there was no significant change in activity level (Tegner) and participation in overhead and/or contact sports observed. There was no correlation between functional outcome and RtA. Limiting, there were alterations in time spent for sporting activities and level of competition observed. But in 50 % those were not related to ACJ symptoms/impairment. Unrelated to successful re-established integrity and function of the ACJ it should be considered that patients decided not return-to-activity but are very content with the procedure.